2015
DOI: 10.1051/0004-6361/201423791
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CN(1-0), HCN(1-0), and HNC(1-0): A possible indicator for a high-mass star formation sequence in the Milky Way

Abstract: Context. CN, HCN, and HNC have been used to discuss the star formation sequence in galaxies, but recent studies of large samples involving these lines did not yet provide convincing results. Aims. We intend to determine whether the global line ratios CN/HCN, CN/HNC, and HCN/HNC can be used to trace the high-mass star formation sequence in the Milky Way. Methods. We performed map observations of CN(1-0), HCN(1-0), and HNC(1-0) toward 38 high-mass star-forming regions, which includes high-mass starless cores (HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Simon et al (2001) determined a kinematic distance of 6 kpc for the GRSMC 45.46+0.05 complex containing the two UC HII regions. Fish et al (2003) and Han et al (2015) obtained near and far kinematic distances for both G45.07+0.13 and G45.12+0.13 of ∼4.0 and ∼8.0 kpc. The estimated far distance is consistent with the previous estimate by Hunter et al (1997) and a more recent one based on the trigonometric parallax method (7.75 ± 0.45 kpc, Wu et al 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Simon et al (2001) determined a kinematic distance of 6 kpc for the GRSMC 45.46+0.05 complex containing the two UC HII regions. Fish et al (2003) and Han et al (2015) obtained near and far kinematic distances for both G45.07+0.13 and G45.12+0.13 of ∼4.0 and ∼8.0 kpc. The estimated far distance is consistent with the previous estimate by Hunter et al (1997) and a more recent one based on the trigonometric parallax method (7.75 ± 0.45 kpc, Wu et al 2019).…”
Section: Introductionmentioning
confidence: 93%
“…This can serve as further evidence that they belong to the same star-forming region and form a physically connected system. According to the results obtained in Han et al (2015), the near and far kinematic distances of G45.07+0.13 and G45.12+0.13 regions are ∼ 4.0 and ∼ 8.0 kpc with tangent point distance of ∼ 6 kpc. The last, far distance estimation, is better consistent with a more recent estimate according to the trigonometric parallax (7.75 ± 0.45 kpc) in Wu et al (2019).…”
Section: Introuctionmentioning
confidence: 63%
“…A molecule that can help differentiate between these scenarios is CN. This molecule can be formed from HCN as a result of intense UV radiation in photodissociation regions (PDRs; e.g., Aalto et al 2002;Baan et al 2008;Han et al 2015). Costagliola et al (2011) found that in the Medusa, globally, CN 1−0 is found at higher intensity than HCN 1−0.…”
Section: Cn As a Tracer Of Radiative Feedbackmentioning
confidence: 99%